When to help juveniles, adults, or both: analyzing the evolutionary models of stage-structured mutualism - Nakazawa, Takefumi; Katayama, Noboru; Utsumi, Shunsuke; Yamawo, Akira; Yamamichi, Masato (Frontiers in Ecology and Evolution, 2023)
Mutualism is common in nature and is crucial for population dynamics, community structure, and ecosystem functioning. Studies have recently pointed out that life-history stage structure (e.g., juveniles and adults) is a key factor to better understand the ecological consequences of mutualism (termed stage-structured mutualism). Despite the potential importance, little is known about what kinds of stage-structured mutualism can evolve and when it is likely to occur. Here, we theoretically investigated how a mutualistic partner species should allocate efforts of mutualistic associations for different life-history stages of its host species to maximize its fitness. We assessed the partner’s optimal strategy by using a one host–one partner model with the host’s juvenile-adult stage structure. The results showed that different forms of stage-structured mutualism can evolve, such as juvenile-specialized association, adult-specialized association, and inter-stage partner sharing (i.e., the partner associates with both the juvenile and adult stages of the host) depending on the shape of association trade-off, i.e., how much association with one stage is weakened when the partner strengthens its association with the other stage. In general, stage-specialized association (either juvenile-specialized or adult-specialized association) tends to evolve when being associated with that stage is relatively beneficial. Similarly, adult-specialized association tends to evolve if it is relatively beneficial. Meanwhile, when the association trade-off is weak, inter-stage partner sharing can occur if the mutualistic benefits of juvenile-specific and adult-specific associations are sufficiently large. We also found that when the association trade-off is strong, alternative stable states occur in which either juvenile-specialized or adult-specialized associations evolve depending on the initial trait value. These results suggest that pairwise interspecific mutualism is more complicated than previously thought, implying that we may under- or overestimate the strength of mutualistic interactions when looking at only certain life-history stages. This study provides a conceptual basis for better understanding the mechanisms underlying ontogenetic shifts of mutualistic partners and more complex mutualistic networks mediated by the life-history stages of organisms and their stage-structured interactions.